A comparative analysis of Hungarian football, handball and ice hockey game officials` concussion recognition ability - Nagy, A.; Kiss, C.; Dolnegó, B.; Tóth, L.; Gécz, G. (Cognition, Brain, Behavior, 2019)
The objective of the present study was to assess and compare Hungarian football, handball and ice hockey game officials` concussion recognition ability. A total of 133 game officials were evaluated using the Concussion Recognition Questionnaire. At the time of the assessment, all participants were working in the highest-level Hungarian league of their respective sports. The findings showed that ice hockey game officials recognized more true symptoms and signs of concussion compared to handball game officials, while no significant difference was found in recognizing false symptoms. Importantly, game officials` previous personal experience of concussion did not influence their ability to recognize concussion symptoms. These findings have crucial practical implications, since they highlight the importance of improving game officials` knowledge of concussion and their ability to recognize related symptoms in order to prevent negativephysical health outcomes and to create a safe playing environment.